The relation of parent alcohol disorder to young adult drinking outcomes mediated by parenting: Effects of developmentally limited versus persistent parent alcohol disorder - Sternberg, Ariel (Drug Alcohol Depend, 2018)
BACKGROUND: Parent alcohol use disorder (AUD) is a well-established risk factor for the development of offspring AUD and is associated with poor parenting. However, few studies have examined heterogeneity in trajectories of parental AUD and its influence on adolescent offspring drinking, and no studies to date have considered the differential risk to offspring conferred by parental AUDs that are limited to early adulthood. Specifically, AUDs limited to the period of emerging adulthood may confer less risk to a child’s environment as recovery following emerging adulthood coincides with the typical ages of entry into the parenting role. The present study tested whether parental AUDs developmentally limited to emerging adulthood (DLAUD) transmit less risk for alcohol problems and alcohol consumption in offspring compared to offspring of parents with AUDs spanning across multiple developmental periods (persistent AUD), as mediated by positive parenting strategies. METHOD: Pathways were examined using longitudinal mediation models (N=361) comparing offspring with parental DLAUD, persistent AUD, and no AUD. RESULTS: Parents with DLAUD do not transmit the same risk for alcohol problems to offspring as parents with persistent AUD (B=0.173, SE=0.067, p < .05); more offspring alcohol problems were associated with persistent AUD than with DLAUD. Positive parenting mediated the transmission of risk from parental AUD to offspring alcohol problems (B=0.040, SE=0.019, p < .05) and consumption (B=0.019, SE=0.011, p < .05) only when comparing persistent AUD vs. no parental AUD. CONCLUSION: Findings suggest that the developmental period in which parents’ recovery occurs is a useful way to categorize “recovered” AUDs versus current AUDs.